1971
DOI: 10.1177/00220345710500043301
|View full text |Cite
|
Sign up to set email alerts
|

131I Concentration in Submandibular Salivary Glands of Rats and Mice

Abstract: In a recent report Esposito (J Dental Res 49: 459, 1970) studied the time course of iodide concentration in the submaxillary gland; he used the rat as his experimental animal. Although iodide is concentrated in salivary glands of humans and other species (B. COHEN and N. B. MYANT, J Physiol 145:595, 1959 and Sci 33:425, 1967), previous studies have shown that iodide is not concentrated in submandibular saliva (J Physiol 145:595, 1959) or in the submandibular salivary gland, in vivo or in vitro (K. BROWN-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Our data (illustrated in Figure 1) showed that iodide uptake by the salivary glands is observed in mouse models, but not in rats, as expected from the literature 58 . In humans, iodine accumulations in the salivary glands are mainly observed in the parotid and submandibular glands 59 .…”
Section: Discussionsupporting
confidence: 89%
“…Our data (illustrated in Figure 1) showed that iodide uptake by the salivary glands is observed in mouse models, but not in rats, as expected from the literature 58 . In humans, iodine accumulations in the salivary glands are mainly observed in the parotid and submandibular glands 59 .…”
Section: Discussionsupporting
confidence: 89%